Tissue Factor Pathway Inhibitor Levels During Veno-Arterial Extracorporeal Membrane Oxygenation in Adults. Issue 8 (August 2021) - Mazzeffi, Michael; Judd, Miranda; Rabin, Joseph; Tabatabai, Ali; Menaker, Jay; Menne, Ashley; Chow, Jonathan; Shah, Aakash; Henderson, Reney; Herr, Daniel; Tanaka, Kenichi
Abstract : Tissue factor pathway inhibitor (TFPI) has multiple anticoagulant properties. To our knowledge, no studies have measured TFPI levels in adult veno-arterial (VA) extracorporeal membrane oxygenation patients. We hypothesized that adult VA ECMO patients would have increased TFPI levels and slowed tissue factor triggered thrombin generation. Twenty VA ECMO patients had TFPI levels and thrombin generation lag time measured on ECMO day 1 or 2, day 3, and day 5. TFPI levels and thrombin generation lag time were compared against healthy control plasma samples. Mean TFPI levels were significantly higher in ECMO patients on ECMO day 1 or 2 = 81, 877 ± 19, 481 pg/mL, day 3 = 73, 907 ± 26, 690 pg/mL, and day 5 = 77, 812 ± 23, 484 pg/mL compared with control plasma = 38, 958 ± 9, 225 pg/mL ( P < 0.001 for all comparisons). Median thrombin generation lag time was significantly longer in ECMO patients on ECMO day 1 or 2 = 10.0 minutes [7.5, 13.8], day 3 = 9.0 minutes [6.8, 12.1], and day 5 = 10.7 minutes [8.3, 15.2] compared with control plasma = 3.6 minutes [2.9, 4.2] ( P < 0.001 for all comparisons). TFPI is increased in VA ECMO patients and tissue factor triggered thrombin generation is slowed. Increased TFPI levels could contribute to the multifactorial coagulopathy that occurs during ECMO.